If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4 + 2x)(5 + 2x) = 56 Multiply (4 + 2x) * (5 + 2x) (4(5 + 2x) + 2x * (5 + 2x)) = 56 ((5 * 4 + 2x * 4) + 2x * (5 + 2x)) = 56 ((20 + 8x) + 2x * (5 + 2x)) = 56 (20 + 8x + (5 * 2x + 2x * 2x)) = 56 (20 + 8x + (10x + 4x2)) = 56 Combine like terms: 8x + 10x = 18x (20 + 18x + 4x2) = 56 Solving 20 + 18x + 4x2 = 56 Solving for variable 'x'. Reorder the terms: 20 + -56 + 18x + 4x2 = 56 + -56 Combine like terms: 20 + -56 = -36 -36 + 18x + 4x2 = 56 + -56 Combine like terms: 56 + -56 = 0 -36 + 18x + 4x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-18 + 9x + 2x2) = 0 Factor a trinomial. 2((-6 + -1x)(3 + -2x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5Solution
x = {-6, 1.5}
| V-8(v+6)=-97 | | 1x=3-x | | 2x^3+x^2+6=0 | | -14+3(x+5)=7(2x+4)+x | | 3p^2(2p+1)=0 | | 8a^2-8=728 | | 5c+3=48 | | 9(6y-5)(2y+3)=0 | | x-139=81-9x | | y=22+9*-2 | | 12-2e=7e+8 | | 12x^2-3x-54=0 | | x=3x-50 | | E^8=2m+3 | | 20(y-4)-4(7y+8)=-16(y+4) | | 3x-y=-22 | | Ln(3x+5)=6 | | x^3-8x^2+32x-64=0 | | 8x-15=-15 | | 2x-y=-16 | | -m-6=3m+14 | | 2y^2-20y+45=x | | c=4n | | 6+8z=7z+4 | | 3x+9=27-9x | | a^2-a+156= | | 36-4g=8 | | -7n-5+2n-5(5n+1)=0 | | 4x+10=10-6x | | 3x-10=5x-10 | | 5+11x=95 | | (5+2i)+(3+6i)= |